Thermostable cellulases: Structure, catalytic mechanisms, directed evolution and industrial implementations. (November 2021) - Akram, Fatima; Haq, Ikram ul; Aqeel, Amna; Ahmed, Zeeshan; Shah, Fatima Iftikhar
Abstract: From an anthropocentric point of view, human culture has been intricately involved in harnessing the potential of lignocellulosic feedstock to bring the bio-competitive alternative of fossil-based fuel resources. In today's scenario, the impact of hyperthermophiles and their enzymes has been intensely investigated for implementation in various high-temperature biotechnological processes. Already characterized archaeal and eubacterial cellulolytic glycoside hydrolase have shown highly impressive catalytic structures and mechanisms. Several sequence and structural factors have simultaneously been proposed to contribute towards the augmented stability of thermophilic proteins. However, state-of-the-art technologies like the rational designing approach and mechanism of directed evolution have emerged as critical toolkits for broadened industrial applications of recombinant proteins. This manuscript discusses the cellulase engineering techniques to enhance the biological production and stability of thermostable cellulolytic enzymes. Highlights: Archaea and eubacteria are a cocktail of thermostable cellulolytic enzymes. Molecular conformation of thermozymes has made them a potent sustainable tool. Protein engineering has filled the gaps in thermophilicity of mesophiles. Cellulosome mediated approach offers better results in biomass hydrolysis. Thermostable cellulases promise environmental, medical and economic sustainability.